THE SLUM COMMUNITY AND CHILDREN STREET VENDOR IN QUEZON CITY, METRO MANILA: LESSON FOR PALEMBANG CITY - Syaifudin Zakir (Program Studi Kependudukan, Pascasarjana Universitas Sriwijaya, 2013)
Development as a freedom, that was conceptualized by Amartya Sen is still need a long process in application and practice especially in the development countries. Philippines as the neighborhood country to Indonesia have the long history how to help the urban poor community who live squatter in the slum area with the Participatory Development Research. This research paper is trying to describe the slum community and the children street vendor in the Loyola Heights Barangay as the two major problems in this barangay. Even one and another are unconnected but this incident is very contrast when we compare with the whole area as to the upper class residential. The slum community and the children street vendor in this area is a real picture of the symbioses and conflict pattern of the urban society, it also the depiction of the dominant class passes the public interest in Loyola Heights Barangay.